Social Capital Moderating Roles towards Relationship of Motives, Personality and Organizational Citizenship Behavior: Cases in Indonesian Banking Industry - Ariani, D. Wahyu (UI Scholars Hub, 2010)
The goal of this research is to test social capital as the moderating variables of the relationship model between core self-evaluation personality, motives, and organizational citizenship behavior. The research integrates the use of atribution, social exchange, core self evaluation theories, and two raters of organizational citizenship behavior. A survey is conducted by using questionnaires from the previous research. The questionnaires were sent to 128 brances of the bank industry located in 16 major cities in Java. The samples consisted of 636 tellers andd 129 head tellers. Validity and reliability tests were used to evaluate the questionnaire contents. The Structural Equation Modelling (SEM) was employed to test the relationship among the variables. The results proved that social capital moderates the relational model between core self-evaluation personality, organizational concern motives, pro-social values motives, impression management motives, and organizational citizenship behavior. The results also show that self-rating and supervisor-rating differ significantly from respect to organizational citizenship behavior. Both are valid and have an equal effect on the organizational citizenship behavior. A thorough discussion on the relationship among the variables as well as on self and supervisor-rating is presented in this paper.